2020
DOI: 10.1042/bcj20180734
|View full text |Cite
|
Sign up to set email alerts
|

RirA of Dinoroseobacter shibae senses iron via a [3Fe–4S]1+ cluster co-ordinated by three cysteine residues

Abstract: In the marine bacterium, Dinoroseobacter shibae the transcription factor rhizobial iron regulator A (RirA) is involved in the adaptation to iron-limited growth conditions. In vitro iron and sulfide content determinations in combination with UV/Vis and electron paramagnetic resonance (EPR) spectroscopic analyses using anaerobically purified, recombinant RirA protein suggested a [3Fe–4S]1+ cluster as a cofactor. In vivo Mössbauer spectroscopy also corroborated the presence of a [3Fe–4S]1+ cluster in RirA. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…Interestingly neither RpoE (Dshi_3423) nor RpoH1 (Dshi_2978) and RpoH2 (Dshi_2609) that play an essential role in adaptation to photooxidative stress were significantly induced in response to the different oxidants applied here. The expression pattern of RirA in response to different oxidants and the observed phenotypic changes of the rirA mutant support the notion that D. shibae RirA is a global transcriptional regulator that possibly senses oxidative stress via an iron sulfur cluster that has recently been shown to be oxygen labile [48]. It represses or activates the expression of genes involved in multiple cellular processes such as protein and DNA repair, energy metabolism and several transport processes and may thus confer adaptive resistance to oxidative stress.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Interestingly neither RpoE (Dshi_3423) nor RpoH1 (Dshi_2978) and RpoH2 (Dshi_2609) that play an essential role in adaptation to photooxidative stress were significantly induced in response to the different oxidants applied here. The expression pattern of RirA in response to different oxidants and the observed phenotypic changes of the rirA mutant support the notion that D. shibae RirA is a global transcriptional regulator that possibly senses oxidative stress via an iron sulfur cluster that has recently been shown to be oxygen labile [48]. It represses or activates the expression of genes involved in multiple cellular processes such as protein and DNA repair, energy metabolism and several transport processes and may thus confer adaptive resistance to oxidative stress.…”
supporting
confidence: 68%
“…Detailed transcriptional analyses of hemB2 already suggested that only at low iron conditions, the absence of RirA led to derepression of hemB2 transcription. Under high iron conditions, IscR may be the major repressor of hemB2 transcription [48]. Data presented here provide first evidence that this might be the case not only for HemB2 but also for other proteins associated with the iron metabolism (e. g. SOUL heme-binding protein Dshi_0086, ABC-type cobalamin/Fe3+-siderophores transport protein FhuA, hemin import ATP-binding protein HmuV and hemin-binding periplasmic protein HmuT) and has to be analysed in more detail.…”
Section: Plos Onementioning
confidence: 99%
“…The oxidized clMagR WT was S = 1/2 species, characterized by a rhombic EPR signal with g values at g 1 = 2.016, g 2 = 2.002, and g 3 = 1.997 (Fig. 1 d) which disappeared at 45 K, suggesting the presence of [3Fe–4S] 1+ cluster 47 , 48 . After reduced with sodium dithionite (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Again, both monomeric and dimeric forms of the protein were observed by native MS 45 45 The observation of [3Fe-4S] clusters following preparation for native MS, which involves gel filtration, was consistent with EPR observations (Fig 2b). 45,75 The physiological significance of [4Fe-4S] RirA was strongly supported by the demonstration that this form of the protein binds IRO box sequences. Exposure to low iron conditions initiates loss of iron to initially generate a [2Fe-2S] form, which exhibits much weaker DNA-binding affinity before degrading further to apo-RirA, which does not bind DNA.…”
Section: 3mentioning
confidence: 99%